Analisis Komparasi Pendapatan dan Efisiensi Penggunaan Modal Usaha Udang Vaname (Litopenaeus vannamei) Berdasarkan Perbedaan Sistem Budidaya di Kabupaten Kolaka - Hadi Mekuo; Bahari Bahari; Bahtiar Bahtiar; Megawati Megawati (Jurnal Sosio Agribisnis, 2020)
The cultivation of Vaname shrimp in Towua I Village, Wundulako District, Kolaka Regency is carried out using 2 cultivation systems, namely intensive and semi-intensive systems. The purpose of this study was to analyze the efficiency of using capital in the Vaname shrimp culture, and to analyze the differences in the income of Vaname shrimp farming between intensive and semi intensive systems. The study location was chosen purposively. The total population is 129 cultivators, consisting of 92 semi-intensive cultivators and 37 intensive cultivators. Sampling was carried out by cluster random sampling method, with a total sample of 16 intensive system cultivators and 40 semi-intensive system cultivators. The data analysis method used is the Revenue-Cost Ratio (R / C) analysis and t-test. The results of the study showed that the Vaname shrimp culture using the semi-intensive system (R-C ratio = 1.59) was more efficient in the use of capital than the intensive system (R / C = 1.42). The income of intensive system of Vaname shrimp cultivation is higher than that of semi intensive system.Key words: Vaname shrimp; intensive and semi intensive; difference in income